1992
DOI: 10.3109/10715769209083145
|View full text |Cite
|
Sign up to set email alerts
|

Modification of thein vitroCytotoxicity of Hydrogen Peroxide by Iron Complexes

Abstract: The effect of a range of iron chelates on the cytotoxicity of H2O2 was studied on a mammalian epithelial cell line. Iron complexes which were internalised enhanced the cytotoxicity of H2O2 measured by delayed thymidine incorporation. Iron complexed to 8-hydroxyquinoline (Fe/8-HQ) potentiated the cytotoxicity of 50 microM by 38% and Fe/dextran by 23%. Pre-exposure of cells to Fe/dextran at 4 degrees C did not result in any potentiation of H2O2-induced cytotoxicity which we ascribe to failure of the Fe/dextran t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…This would suggest that the presence of iron within the cell poses more risk than any effect on free radical generation in the external milieu. Evidence to support this hypothesis is provided by tissue culture studies showing that the effects of exposure of cells to hydrogen peroxide are ameliorated by the presence of iron in a nonabsorbable form but exacerbated when iron is presented in an absorbable form (24). Although body iron stores were not measured in this study, we found higher concentration of liver iron in our earlier short-term study (17), which suggests that there would have been higher circulating concentrations of iron in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…This would suggest that the presence of iron within the cell poses more risk than any effect on free radical generation in the external milieu. Evidence to support this hypothesis is provided by tissue culture studies showing that the effects of exposure of cells to hydrogen peroxide are ameliorated by the presence of iron in a nonabsorbable form but exacerbated when iron is presented in an absorbable form (24). Although body iron stores were not measured in this study, we found higher concentration of liver iron in our earlier short-term study (17), which suggests that there would have been higher circulating concentrations of iron in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…Conversely, increasing intracellular iron can enhance H 2 O 2 -induced injury as seen with cardiomyocytes [16]. Pre-incubation of the epithelial cell line CNCMI221 with Fe 3+ /8-hydroxyquinoline enhanced the observed cytotoxic effects of H 2 O 2 [17]. It is well known that the primary oxidant generated by the Fenton reaction (H 2 O 2 + Fe 2+ ) is the hydroxyl radical, HO • [18].…”
Section: Introductionmentioning
confidence: 99%
“…The primary cause of radical hydroxyl damage is H 2 O 2 . The quantity of hydroxyl radicals in the body is partially controlled by the cellular antioxidant status (Jonas & Riley, 1992). Cells have their antioxidant types of machinery, which consist of several Phase II detoxification enzymes like glutathione peroxidases (GPXs) and the three superoxide dismutase isoforms (SOD1, SOD2, SOD3) (Masutani & Thioredoxin, 2002).…”
Section: Oxidative Stressmentioning
confidence: 99%